ANALISIS PENGEMBANGAN SARANA PRASARANA OBYEK WISATA ALAM TELAGA NGEBEL DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT - Titis Ariani Mustikawati; Sunarti Sunarti; Edriana Pangestuti (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
This research uses descriptive qualitative method with two problem formulation, that is how is Local Government role (Disbudparpora) in developing tourism infrastructure of Telaga Ngebel and how is the development of infrastructure development in Telaga Ngebel area. Data sources were obtained from informants, observations, documents, and documentation. Data analysis uses four stages: data collection, data reduction, data presentation, and conclusion. Based on research on the role of Disbudparpora in the development of tourism object Ngebel Telaga get results in the planning that includes the attractiveness of tourism, the development of facilities and infrastructure and accessibility, as well as promotional planning. Implementing policies in improving people's welfare on the economic aspect. Participate in making tourism regulations delegated authority to Ngebel village devices implementation of tourism development Ngebel Lake is known to run according to the formulation of planning. Although not all development plans can be implemented, but the thing is already a bit much to bring a much better change in tourism objects Ngebel Lake. Installation of streetlights, dock repairs, orderly and neat programs against street vendors, as well as organizing various events such as music performances and Reyog performances once every two months as an effort to attract tourist arrivals. Keyword : Attractiveness Of Tourism, Development Of Facilities And Infrastructure, Accessibility, Promotional Planning ABSTRAK Penelitian ini menggunakan metode deskriptif kualitatif dengan dua rumusan masalah, yaitu bagaimana peran Pemerintah Daerah (Disbudparpora) dalam mengembangkan sarana prasarana obyek wisata Telaga Ngebel dan bagaimana pelaksanaan pengembangan sarana prasarana di kawasan Telaga Ngebel. Sumber data diperoleh dari informan, observasi, dokumen, dan dokumentasi. Analisis data menggunakan empat tahap yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan penelitian mengenai peran Disbudparpora dalam pengembangan obyek wisata Telaga Ngebel mendapatkan hasil dalam perencanaan yang meliputi daya tarik wisata, pembangunan sarana dan prasarana serta aksesibilitas, dan juga perencanaan promosi. Mengimplementasikan kebijakan dalam meningkatkan kesejahteraan masyarakat pada aspek ekonomi. Berperan dalam membuat peraturan pariwisata yang dilimpahkan kewenangannya kepada perangkat desa Ngebel. Pelaksanaan pengembangan obyek wisata Telaga Ngebel diketahui berjalan sesuai rumusan perencanaan. Meskipun belum semua perencanaan pengembangan dapat terlaksan, namun hal tersebuut sudah sedikit banyak membawa perubahan yang jauh lebih baik pada obyek wisata Telaga Ngebel. Pemasangan lampu jalan, perbaikan dermaga, program tertib dan rapi terhadap pedagang kaki lima, serta penyelenggaraan berbagai acara seperti pentas musik dan pentas Reyog setiap dua bulan sekali sebagai upaya dalam menarik kunjungan wisatawan. Kata Kunci : Daya Tarik Wisata, Pembangunan Sarana Dan Prasarana, Aksesibilitas, Perencanaan Promosi